Anxiety and Difficulties of Infertile Women. The Moderating Role of Attachment Pattern - Diana Antonia Iordăchescu; Alina Estera Boca; Corina Ioana Paica; Paul Bălănescu; Anca Maria Panaitescu; Gheorghe Peltecu; Corina Gică; Alexandra Buică; Nicolae Gică (Clinical and Experimental Obstetrics & Gynecology)
Background: The present study focuses on examining the association between attachment pattern, anxiety and perceived infertility-related difficulties of women with fertility concerns. Also, the study explores the moderating role of attachment in the relationship between infertility duration and perceived difficulties, but also in the relationship between anxiety and infertility difficulties. Methods: Our study is a descriptive, correlational one. Quantitative data was used, employing transversal and quantitative analysis, thus proving the study to be an experimental one. Survey data was obtained from a total of 240 women with fertility problems (N = 240), aged between 22 and 46 years old (M = 32.71, SD = 4.85). Results: Results show that participants with a pattern of secure attachment had obtained lower scores on state anxiety, trait anxiety and the difficulties scale compared to those with an avoidant one. Also, women that had undergone repeated in vitro fertilization procedures had significantly higher avoidant attachment scores than those that had undergone a single treatment procedure. Another important result is that avoidant attachment moderates the relationship between trait-anxiety and the global difficulties perceived by infertile women. Conclusions: The results of the study show that women can be deeply affected by failed fertilization attempts and repeated miscarriages; as a consequence, they might feel powerless because they cannot become mothers, which leads, over time, to feelings of anxiety, depression, especially when they do not benefit from social support and have not developed resilience mechanisms.